Collisional excitation of water by hydrogen atoms. Issue 3 (24th November 2014) - Daniel, F.; Faure, A.; Dagdigian, P. J.; Dubernet, M.-L.; Lique, F.; Forêts, G. Pineau des
Abstract: We present quantum dynamical calculations that describe the rotational excitation of H2 O due to collisions with H atoms. We used a recent, high-accuracy potential energy surface, and solved the collisional dynamics with the close-coupling formalism, for total energies up to 12 000 cm −1 . From these calculations, we obtained collisional rate coefficients for the first 45 energy levels of both ortho- and para-H2 O and for temperatures in the range T  = 5–1500 K. These rate coefficients are subsequently compared to the values previously published for the H2 O/He and H2 O/H2 collisional systems. It is shown that no simple relation exists between the three systems and that specific calculations are thus mandatory.